Protection of wakaf-zakat properties for the needy and poor via takaful - Mohd Fauzi, Puteri Nur Farah Naadia; Abdul Rashid, Khairuddin (Kolej Universiti Islam Antarabangsa Selangor, 2017)
In Islam, wakaf and zakat are instruments aimed at helping the needy and poor. Consequently, wakaf and zakat authorities design schemes including funding the building of new properties for the needy and poor or repairing their existing properties. Naturally, the completed properties and their contents are exposed to a variety of risks such as fire and natural disasters, hence the need for appropriate protection. According to Shariah, such protection is allowed through takaful. However, literature is lacking on the provision of risk protection of wakaf and zakat properties and contents therein. As such little is known about the concept of risk protection of wakaf and zakat properties designated or occupied by the needy and poor. This paper endeavours to unveil the concept of risk protection of wakaf and zakat funded properties belonging to or occupied by the needy and poor, highlights its importance and identify the means available to the wakaf and zakat authorities for securing the required risk protection. The paper is conceptualized through desk study and review of wakaf and zakat authorities’ manual guidelines and reports on the provision of takaful as protection of wakaf and zakat funded properties and contents therein. Results from the study suggest that (i) importance of takaful to protect properties are acknowledged, but there appears lackadaisical attitudes in terms of the important of takaful in protecting properties belonging to wakaf and zakat authorities and occupied by the needy and poor; (ii) unclear provision of takaful as stated in wakaf and zakat authorities’ reports in terms of management and procurement, operations, and amount allocated and spent for takaful contribution in protecting wakaf properties as well as assisting the relevant asnaf via zakat fund; and (iii) authorities lack forward thinking in terms of the need for such risk protection and therefore unable to design schemes that extend the assistance given to the needy and poor in providing the necessary funds to pay for the contributions on their behalf. This paper is considered significant in terms of (i) highlighting the need for risk protection of properties belonging to or occupied by the needy and poor so that should unfortunate events occur, the needy and poor would not be ‘out of pocket’ and the authorities do not have to dig deeper into their coffers for the necessary funds needed for repairs and rebuilding; and (ii) the idea of wakaf, zakat and takaful to collaborate is considered a novelty in effort to reduce the cost of contributions and to achieve efficiency and effectiveness in the services provided thereto.